ANALISIS KEMAMPUAN SISWA DALAM MENYELESAIKAN SOAL-SOAL BANGUN RUANG - Rika Rahmawati (Universitas Muhammadiyah Lampung, 2020)
This research is a qualitative descriptive research. The population is all students of class VIII even semester of SMP Negeri 5 Bandar Lampung totaling 187 students. Sampling technique a. The technique used in this study is the cluster random sampling technique. Because the population is more than 100 people, the authors determine the sample in this study is 16% or as many as 30 students. This study aims to: (1) determine the percentage of students' abilities in solving spatial problems, (2) find out the causes of students' difficulties in solving spatial problems, (3) find out how to overcome students' difficulties in solving spatial problems. . Based on the results of the study, it can be concluded: (1) students who are able to solve spatial problems are 62.99% and those who have difficulty are 37.01%, (2) the causes of students experiencing difficulties in solving spatial problems are (1) students do not understand the concept of building space in applying it to a problem, (2) students are not careful in working on every question that exists. As for how to overcome student difficulties, namely: (1) increasing students' ability to understand the concept of building space by giving emphasis when delivering material (2) more evaluation in the form of practice questions at the end of each learning activity, (3) giving homework for finalize the material that has been presented.